Visions of the Islamic State: Fazlur Rahman and Islamic Nomocracy - Peterson, Ben (Islamic Studies, 2023)
Proponents of reform in Islamic political thought and practice frequently describe the work of Fazlur Rahman, the twentieth-century modernist scholar of Islam, and his method of Qur’ānic interpretation as a source of intellectual and political rejuvenation for contemporary Muslims. This article describes the ethicist underpinnings and content of Fazlur Rahman’s democratic vision of the Islamic state, as expressed in his major writings of the 1960s, and contrasts that vision with other proposals for establishing an Islamic nomocracy in contemporary Pakistan. The context of state building fundamentally shaped Fazlur Rahman’s constitutional theory, and his arguments expressly repudiate the traditional, independent position of the religious elites or ‘ulamā’ and aim at absorbing them into the state apparatus. This article contributes to the literature by explicating in a systematic way Fazlur Rahman’s constitutional theory, clearly drawing the connection between the ethicist content of his double-movement hermeneutic with the statism of his vision of Islamic democracy. Fazlur Rahman’s theory fails to establish a framework for an Islamic nomocracy, posing a significant challenge for advocates of intellectual and constitutional reform who champion the ethicist approach.